Participation of Local Farmer’s Organizations in Supporting the Cocoa Plant Revitalization Program - masitah, Masitah; Campina Illa Prihantini; Nursalam; Khaerunnisa; Dennis Mark Onuigbo (Indigenous Agriculture, 2023)
Cacao is a promising plant for farmers as one of the plantation crops that plays a significant role for the national economy by providing employment, income, and foreign exchange source and encouraging regional and agro-industrial developments. In the revitalization program of cacao plants at North Kolaka Regency, Southeast Sulawesi. This activity becomes The Ministry of Agriculture’s effort to return the glory of Indonesian plantation commodities by distributing free excellent seeds to farmers. This study aimed to determine the Local Farmer Organization’s participation in supporting the cacao plant revitalization program in Central Pekue District, North Kolaka Regency. Methods used for data analysis were qualitative and quantitative descriptive methods with a Likert scale. The data were composed of primary and secondary data. In terms of the organization participation of farmers in supporting the cocoa plant revitalization program, this study describes that the Local Farmer Organization as farmer groups mainly plays the role of an information-sharing forum, a discussion place, a learning place, and a collaborative place with an average value of 58.72.